Real world treatment utilization patterns in patients with castration-resistant prostate cancer. (4th July 2021) - Vigneswaran, Hari T.; Warnqvist, Anna; Andersson, Therese M. L.; Leval, Amy; Eklund, Martin; Nordström, Tobias; Eloranta, Sandra; Schain, Frida; Dearden, Lindsay; Liwing, Johan; Mehra, Maneesha; Nair, Sandhya; et al.
Abstract: Background: Studies describing treatment utilization for castration-resistant prostate cancer (CRPC) are limited. We aimed to describe the treatment utilization of a contemporary population-based CRPC cohort between 2006 and 2016. Methods: We identified 1699 men with a PC diagnosis between 2005 and 2015, who developed CRPC between 2006 and 2015 in the Stockholm region of Sweden. Demographic information, stage and grade at PC diagnosis, stage at CRPC, prostate-specific antigen (PSA) nadir, PSA doubling time, treatment utilization rate within 1 year of CRPC diagnosis, reason for stopping therapy, treatment sequence trajectory, overall and PC specific survival was described. Results: Treatment for men with de novo metastatic disease ( n = 463) was 32%, treatment for men with progressive metastatic disease after PC diagnosis ( n = 66) was 44%, treatment for men with nonmetastatic CRPC ( n = 113) was 34% and treatment for those with an unknown stage at time of CRPC diagnosis ( n = 857) was 12%. Docetaxel was used in 39%, abiraterone acetate plus prednisone in 15%, enzalutamide in 13%, cabazitaxel in 11% and radium-223 in 5% of treatments. Treatment increased from 22% in 2006–2009 for metastatic cancer to 50% in 2013–2015 ( p < .001). Factors associated with treatment were an unknown stage at diagnosis (OR: 0.3, 95% CI: 0.2–0.4), age ≥75 years (OR: 0.2, 95% CI: 0.1 − 0.3), PSA doubling time >3 months (OR: 0.4, 95% CI: 0.3 − 0.6) and a diagnosis between 2013 and 2015 (OR: 3.4, 95% CI: 2.0 − 5.8). Conclusions: Despite treatment availability, in this large real-world cohort we found treatment utilization to remain low.